Exploring Technological Pedagogical and Content Knowledge (TPACK) in English Language Classroom Setting: In-Service English Teachers’ Perspectives - Galuh Dara Kirana; Salim Nabhan (Universitas Muhammadiyah Jember, 2021)
Technological Pedagogical and Content Knowledge (TPACK) is one of today’s frameworks that integrates technology in the teaching and learning process. However, little research has been done related to the investigation of in-service teachers’ TPACK, specifically in English language classroom setting. Therefore, this study aims at exploring TPACK in English language classroom from the prespectives of in-service English teachers. Qualitative case study was involved as the approach of the study. The researchers utilized the triangulation of data sources including interview, observation, and document to get the data from in-service English teachers’ as the respondents of the study. The data acquired were then transcribed verbatim and analyzed using thematic analysis. The current study shows that there are three main themes as findings comprising English teachers’ understanding toward TPACK, the process of acquiring TPACK, and the English teachers’ challenges toward TPACK. The English teachers had a diverse understanding pertaining TPACK, and they owned various strategies in acquiring TPACK. However, the teachers faced challenges in implementing TPACK. This study migh have implications in providing the direction of English teachers’ professional development.